2022
DOI: 10.35379/cusosbil.1037173
|View full text |Cite
|
Sign up to set email alerts
|

Özçeki̇m Tutum Ölçeği̇’ni̇n Üni̇versi̇te Öğrenci̇leri̇nde Geçerli̇k Ve Güveni̇rli̇k Çalişmasi

Abstract: Bu araştırmanın amacı Özçekim Tutum Ölçeği'nin (ÖTÖ) üniversite öğrencilerinde geçerlik ve güvenirlik çalışmasını yapmaktır. Çalışmada toplam 210 üniversite öğrencisinden veri toplanmıştır. Verilerin toplanmasında ÖTÖ ve Selfitis Davranış Ölçeği (SDÖ) kullanılmıştır. Veriler, Keiser-Meyer Olkin ve Bartlett küresellik testi, Doğrulayıcı Faktör Analizi (DFA), ilişkisiz örneklemler için t-testi ve Pearson korelasyon katsayısı teknikleriyle çözümlenmiştir. DFA sonuçlarına göre ÖTÖ'nün 28 maddesinin faktör yüklerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…However, some studies also found a significant difference between gender and problem-solving skills (Barahmand, 2010;Otacıoğlu, 2007). Çam and Tümkaya (2006), on the other hand, found that there was no significant difference in constructive problem solving and not taking responsibility subdimensions according to gender, but there was a difference in negative approach to problem, self-confidence and persistent-persistent approach. The reason why women's problem solving scores are lower than men's; This may be due to their elaborative way of thinking and the fact that girls are raised more protectively and their problem-solving skills are weaker than boys.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, some studies also found a significant difference between gender and problem-solving skills (Barahmand, 2010;Otacıoğlu, 2007). Çam and Tümkaya (2006), on the other hand, found that there was no significant difference in constructive problem solving and not taking responsibility subdimensions according to gender, but there was a difference in negative approach to problem, self-confidence and persistent-persistent approach. The reason why women's problem solving scores are lower than men's; This may be due to their elaborative way of thinking and the fact that girls are raised more protectively and their problem-solving skills are weaker than boys.…”
Section: Discussionmentioning
confidence: 88%
“…The reason why women's problem solving scores are lower than men's; This may be due to their elaborative way of thinking and the fact that girls are raised more protectively and their problem-solving skills are weaker than boys. The fact that girls are more insistent, hasty and persistent in solving interpersonal problems compared to boys is a negative thought that prevents the solution of the problem (Çam & Tümkaya, 2006;Öğülmüş, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ulusal ve uluslararası akademik yayınlar incelendiğinde yetkinlik konusunun hemşirelik (Gözüm ve Aksayan, 1999;Karahan ve Kav, 2018;Ülker, 2018), psikoloji (Çelikkaleli ve Çapri, 2008;Demirel, 2013;Pamukçu ve Demir, 2013), öğretmenlik (Arslanbaş, 2011;Özkahraman, 2012), insan kaynakları ve yönetim bilimleri (Keçecioğlu ve Kelgökmen, 2003;Liedtke, 2016) gibi farklı mesleki alanlarda işlenmiş olduğu görülmektedir. Kavramın farklı meslekler için araştırılıyor olması, terimi her mesleğin kendi yaklaşımına göre değerlendirmesine zemin hazırlamakta ve kullanım alanını genişlemektedir (Çetinkaya, 2009).…”
Section: Introductionunclassified